2020
DOI: 10.1101/2020.09.15.20195339
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association among income loss, financial strain and depressive symptoms during COVID-19: evidence from two longitudinal studies

Abstract: Background. The COVID-19 pandemic has major ramifications for global health and the economy, with growing concerns about economic recession and implications for mental health. Here we investigated the associations between COVID-19 pandemic-related income loss with financial strain and mental health trajectories over a 1-month course. Methods. Two independent studies were conducted in the U.S and in Israel at the beginning of the outbreak (March-April 2020, T1; N = 4 171) and at a 1-month follow-up (T2; N = 1 5… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 25 publications
8
46
0
Order By: Relevance
“…Furthermore, depressive symptoms can stem from stressful events, such as loss of a loved one and economic difficulties. With death tolls increasing (Gallagher et al, 2020;Yildirim and Güler, 2020) and growing concerns about an economic recession caused by COVID-19 (Hertz-Palmor et al, 2020;Wilson et al, 2020), these events have been shown to be contributors to increased depression rates and its associated symptoms (Gallagher et al, 2020;Hertz-Palmor et al, 2020;Wilson et al, 2020;Yildirim and Güler, 2020). During time point 4, the number of people with depressive symptoms was reduced compared to the other time points, and with the start of phase one occurring at this time point, some economic stress may have be alleviated as some people may have been returning to work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, depressive symptoms can stem from stressful events, such as loss of a loved one and economic difficulties. With death tolls increasing (Gallagher et al, 2020;Yildirim and Güler, 2020) and growing concerns about an economic recession caused by COVID-19 (Hertz-Palmor et al, 2020;Wilson et al, 2020), these events have been shown to be contributors to increased depression rates and its associated symptoms (Gallagher et al, 2020;Hertz-Palmor et al, 2020;Wilson et al, 2020;Yildirim and Güler, 2020). During time point 4, the number of people with depressive symptoms was reduced compared to the other time points, and with the start of phase one occurring at this time point, some economic stress may have be alleviated as some people may have been returning to work.…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that "coronaphobia, " a termed coined by , has led to increases in anxiety because individuals who are anxious about COVID-19 tend to experience a coherent set of mental health and mood disturbances that are triggered by thoughts, information, or news associated with the virus (Evren et al, 2020). Similarly to depressive symptoms, symptoms of anxiety has been positively associated with COVID-19-related stressors including financial worries (Hertz-Palmor et al, 2020;Wilson et al, 2020), deathrelated anxiety (Gallagher et al, 2020;Yildirim and Güler, 2020), disruptions to daily life including academic disruptions (Cao et al, 2020), and ambiguity of when COVID-19 would end (Freeston et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Such interventions may be constrained additionally by the economic effects of the pandemic, and governments must balance economic and health considerations. However, it is notable that personal economic loss during lockdown is associated with worsening of mental health, particularly an increase in depressive symptoms (38), and that explicit consideration of the trade-offs between infective and economic/wellbeing considerations may be required for maximum public benefit (39).…”
Section: Discussionmentioning
confidence: 99%
“…Lower socioeconomic conditions, stressful circumstances, less dental care utilization, and unfavorable oral health–related behaviors have been reported as risk factors for dental pain (Kuhnen et al 2009; Medina-Solís et al 2017; Tsuchiya et al 2019). Under the COVID-19 pandemic, higher anxiety and depression are reported among those who lost their income (Hertz-Palmor et al 2020) and those who had insecure jobs (Ganson et al 2021). People in worsened socioeconomic circumstances may be unable to afford costs associated with good oral health such as dental fees.…”
Section: Introductionmentioning
confidence: 99%